Guidance on home blood pressure monitoring: A statement of the HOPE Asia Network - Kario, Kazuomi; Park, Sungha; Buranakitjaroen, Peera; Chia, Yook Chin; Chen, Chen Huan; Divinagracia, Romeo; Hoshide, Satoshi; Shin, Jinho; Siddique, Saulat; Sison, Jorge; Soenarta, Arieska Ann; Sogunuru, Guru Prasad; et al. (Wiley, 2018)
Hypertension is an important modifiable cardiovascular risk factor and a leading cause of death throughout Asia. Effective prevention and control of hypertension in the region remain a significant challenge despite the availability of several regional and international guidelines. Out-of-office measurement of blood pressure (BP), including home BP monitoring (HBPM), is an important hypertension management tool. Home BP is better than office BP for predicting cardiovascular risk and HBPM should be considered for all patients with office BP ≥ 130/85 mm Hg. It is important that HBPM is undertaken using a validated device and patients are educated about how to perform HBPM correctly. During antihypertensive therapy, monitoring of home BP control and variability is essential, especially in the morning. This is because HBPM can facilitate the choice of individualized optimal therapy. The evidence and practice points in this document are based on the Hypertension Cardiovascular Outcome Prevention and Evidence (HOPE) Asia Network expert panel consensus recommendations for HBPM in Asia.